French Language Education The Teaching of Culture in the Classroom - Illinois State Office of the Superintendent of Public Instruction, Springfield; Jay, Charles; Castle, Pat; Illinois State Office of the Superintendent of Public Instruction, Springfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Eleven articles focus on the necessity of including cross-cultural studies in language programs in American schools. The notion of culture, it is emphasized, must not be seen as the narrow study of literature, art, music, and philosophy. The articles include: (1) a one act tragedy on the omission of cultural studies in secondary schools, (2) teaching of French culture, (3) culture in FLES programs, (4) culture and student motivation, (5) French music and the mini-lesson in culture, (6) culture at the university level, (7) culture-wide values and assumptions as essential content for levels 1 to 3, (8) a modern college curriculum in French studies, (9) testing and teaching auditory comprehension with pictures, (10) French culture and civilization for high school students, and (11) experiencing culture in the classroom. Several French songs are included. The 1969 Bloomington Conference "An Explanation of 'Levels' of Competence in Foreign Language Learning in French--Levels 1, 2, 3" is found in the appendix. (RL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Area Studies; Articulation (Education); Cultural Background; Cultural Education; Educational Objectives; Evaluation Methods; Fles; Foreign Culture; French; Instructional Program Divisions; Language Instruction; Modern Languages; Relevance (Education); Second Language Learning; Student Attitudes; Student Motivation; Teacher Attitudes; Teaching Methods